2021
DOI: 10.1007/s40843-021-1844-4
|View full text |Cite
|
Sign up to set email alerts
|

Broadband multimodal emission in Sb-doped CaZnOS-layered semiconductors

Abstract: Mechanoluminescent (ML) smart materials are expected to be used in stress sensors, new displays, and advanced flexible optoelectronic devices, because of their unique mechanical-to-light energy conversion properties. However, the narrow-range ML emission characteristics of single materials limit their application scope. In this work, we report on the broadband multimodal emission in Sb-doped CaZnOS layered semiconductors. A series of CaZnOS layer-structured powders with different Sb 3+ doping concentrations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…[18] Importantly, the chemical constitution of ligands and coordination number have significant impacts on the crystal field strength in organic and inorganic manganese metal complexes. [19] The divalent manganese ion with a 3d 5 electron configuration exhibits a 4 T 1 -6 A 1 radiative transition, which is closely related to the crystal field intensity among the various valence states of manganese ions. [20] As shown in Figure 1a, the tetrahedral coordinated Mn(II) species exhibit green emission originating from the 4 T 1 -6 A 1 , while the octahedrally coordinated one exhibits red emission.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[18] Importantly, the chemical constitution of ligands and coordination number have significant impacts on the crystal field strength in organic and inorganic manganese metal complexes. [19] The divalent manganese ion with a 3d 5 electron configuration exhibits a 4 T 1 -6 A 1 radiative transition, which is closely related to the crystal field intensity among the various valence states of manganese ions. [20] As shown in Figure 1a, the tetrahedral coordinated Mn(II) species exhibit green emission originating from the 4 T 1 -6 A 1 , while the octahedrally coordinated one exhibits red emission.…”
Section: Resultsmentioning
confidence: 99%
“…[4] Peng et al reported on mechanoluminescent characteristics of multimodal energy transformation in Sbdoped CaZnOS layered semiconductors. [5] Recently, Yao's group reported an efficient thermochromic phosphor based on the unique ionic 1D-Cu 4 I 6 L 2 hybrid with reversible temperature-dependent crystal transformation, which holds great potential for functional LED illumination. [6] Of the stimuli available, temperature offers numerous attractive features due to its convenient availability, wide modulating range and spatial and temporal control, [7] which is also one of the most fundamental physical parameters in scientific research, industrial production and daily life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, SAOE's ML has characteristic green light, compounding with ML materials having different colors, such as ZnS:Mn or CaZnOS:Mn (orange‐red light) or other stress‐induced luminescent materials will render promising applications. [ 129 , 130 , 131 , 132 , 133 , 134 ] ML materials can also be used as an emergency lighting energy source (Figure 49a–d ). In sports training, it can be used in shoes (Figure 49e,f ), art of fencing (Figure 49g ), diving, [ 135 ] skating (Figure 49h ), ball sports such as squash, ping pong (Figure 49i ), and soccer (Figure 49j ) to display points at which balls strike a surface or goal and used in fencing to visualize the point of a sword in order to improve judgment of the fencing area to calculate the score.…”
Section: Applicationsmentioning
confidence: 99%
“…Given the solid theoretical foundation of conventional Er 3+based ratiometric thermometry approaches and the superb characteristics of ML materials, here we aim to design a framework for solid Er 3+ -based ML thermometry. Considering that CaZnOS is an excellent host matrix for ML and has been well investigated [39][40][41][42][43][44], our idea is demonstrated on CaZnOS:Er 3+ . As shown in Fig.…”
Section: Introductionmentioning
confidence: 98%